Analysis of VSAT System Performance in Security and Communication Integrity of Indonesian Navy Headquarters - Sunu Harnoko; Franciskus Antonius Alijoyo (SEAN Institute, 2023)
The development of satellite communications technology makes it easier for various groups and agencies to send and receive information and maintain confidentiality. In carrying out communications, the Indonesian Navy uses satellite technology in the form of VSAT. VSAT is an abbreviation for